Voluntary internet disclosure in four GCC countries: a study of attributes and determinants. (2015) - Mohamed, Ehab K.A.; Basuony, Mohamed A.K.
The purpose of this paper is to examine the determinants and attributes of voluntary internet disclosure by listed companies in four countries in the Gulf Cooperation Council (GCC). This paper uses archival data from 247 listed companies on the Dubai Financial Market, Qatar Stock Exchange, Muscat Securities Market, and Bahrain Bourse. Binary logistic regression analysis is used to examine the determinants of internet financial reporting. Kruskal-Wallis test is used to examine the differences in disclosure attributes among the four countries. The results of this study reveal that firm size and industry type are the influencing factors that impact internet financial reporting in the GCC. The results reveal that the four countries differ significantly in all the disclosure attributes with the exception of e-mail link. The paper provides insights into corporate internet disclosure in the GCC that will benefit all stakeholders with an interest in corporate reporting in this important region of the world. The results are consistent with previous literature that corporate size is a major determinant of internet financial reporting. This paper is the first to examine factors affecting corporate internet reporting in the GCC and the variance in disclosure attributes among countries in this region.